The stylistics of expressive structure in Al-Sayyab's attempt- A textual study (Journal of the College of Languages (JCL), 2014)
Our research tends to study the poetic attempt of Badr Shakir Al-Sayyab and examine it stylistically, and we suggested his mature collection '' Rain song'' as a pattern for our textual analysis of the poet's attempt. In the beginning , we confirm that branches of applied structures meet to produce poetry such as narration , drama , cinema , mythology , allegory , various religious and historical texts , previous events , and special cumentary events related to work production. If all above-mentioned was complicated and disregarded throughout a single text , the text writer would not secure positive results that might keep open continuity between him and his readers. Therefore , this issue was treated by Al-Sayyab , when we found that his address introduced the concept of existence of hidden address that supports his apparent poetic verses and provides textual wideness to play on intended words , but it conceals them beyond the poetic structures and makes them alternate texts . We preferred our analysis to be textual i.e despite it is related to modern stylistic lesson , it sees stylistics as being more mature to understand romantic texts. We have selected a collection of Al-Sayyab's poetic texts and analyzed them stylistically in conformity with our research.